The effect of temperature factor during heavy ion irradiation on structural disordering of SiC ceramics - Kymbat M. Tynyshbayeva; Artem L. Kozlovskiy (Optical Materials: X)
The paper presents the results of the influence of heavy ion irradiation on the formation of anisotropic distortions of the crystal structure and electron density distribution in SiC ceramics. The assessment of the change in the properties of the damaged layer was carried out using Raman spectroscopy methods, and using data on structural changes obtained using the X-ray diffraction method. The observed alterations in the spectral modes E1(TO), E2(TO) and A1(LO) depending on the irradiation temperature indicate an anisotropic distortion of the structure, which has a clearly expressed dependence on the irradiation temperature, as well as the type of ions used for irradiation. The assessment results of changes in the electron density distribution contingent upon the irradiation temperature for both types of ion irradiation showed a direct correlation between the irradiation temperature growth and the electron density anisotropic distortion caused by the deformation of chemical bonds. In turn, the combination of the effects of thermal heating and ionization processes causes deformation distortion of chemical bonds, which is most pronounced at high irradiation temperatures, for which thermal expansion of the crystal lattice and accelerated diffusion of vacancy defects play a key role in disordering.